Continuité et discontinuité de l’implication des habitants dans les écoquartiers. Le cas de la Zac Pajol à Paris - Camille Gardesse; Isabelle Grudet (Développement Durable et Territoires)
This article concerns the development process for the Pajol ZAC (designated development area) in Paris. For several reasons, this is an exceptional project. Firstly because it emerged through bottom up movements, something only applicable to 8 % of ecodistricts in France. Secondly, because the involvement of the inhabitants took place within a climate of trust. The means created to develop the ZAC provided highly effective forums of exchange and dialogue for the programming, urban master plan and public spaces. These meeting frameworks sought solutions that went much further than the accession and appropriation objectives that generally govern the decisions taken by elected representatives and professionals. Finally, because the involved inhabitants decided to extend their commitment beyond the handover of the buildings by organising cultural events around public amenities or by becoming involved in the Paris Nord Est project. However, despite the presence of one of their representatives in the architectural competition juries, the inhabitants were not invited to participate in the choices made on an architectural level (spatial devices, materials, energy, etc.) which remained within and inter-professional sphere. In that sense, the project illustrates a constant noted in the research carried out in the field of city planning and concerning the participative approach in France : even in projects where the inhabitants are considerably involved, the latter are rarely invited to participate in all aspects of the project development process.